Structure and Tribological Property of TiBN Nanocomposite Multilayer Synthesized by Ti-BN Composite Cathode Plasma Immersion Ion Implantation and Deposition - 吕文泉 王浪平 曹永志 顾至伟 王小峰 闫永达 于福利 (Chinese physics letters, 2016)
A Ti-BN complex cathode is made from Ti and h-BN powders by the powder metallurgy technology, and TiBN coating is obtained by plasma immersion ion implantation and deposition with this Ti-BN composite cathode. The TiBN coating shows a self-forming multilayered nanocomposite structure while with relative uniform elemental distributions. High resolution transmission electron microscopy images reveal that the multilayered structure is derived from different grain sizes in the nanocomposite. Due to the existence of h-BN phase, the friction coefficient of the coating is about 0.25.